A Possible Role of Peptides in the Growth Enhancement of an Industrial Strain of Saccharomyces sp. - Cortes, Dino Paolo (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Individual addition of a commercially available nutritional supplement and a methanol extract from an industrial Saccharomyces sp. strain SMC resulted in the enhanced growth of Saccharomyces sp. strain SMC in minimal medium. Isolation of the growth enhancing components from aqueous extracts of the supplement and the cellular extract was performed using reversed-phase, gel filtration, and ion exchange chromatography. Reversed-phase chromatography using Sep-Pak® vac C18 yielded aqueous washes which elicited increased yeast growth. Gel filtration chromatography of the aqueous washes in a group separation mode using Sephadex G25 gave three distinct groups for the nutritional supplement, and four distinct groups for the cellular extract. Fraction groups that exhibited growth enhancing activity also exhibited high absorbances at all three wavelengths of 214, 260, and 280 nm. Two major fractions which tested positive for growth enhancing activity in succeeding experiments were obtained after passing each of the active GFC groups through a Toyopearl SP 550C cation exchanger column. The active component from the cellular extract did not bind to the cation exchanger. The absorbance data at 214 nm (peptide bond experimental absorbance maximum wavelength), the Bradford assay (showing the presence of proteinaceous matter), and the active component’s inclusion in the Sephadex G25 fractionation range of 1-5 kDa (characteristic of small peptides) suggest that the growth enhancing components of the nutritional supplement and methanol cell extracts are peptides.